Masjid An-nahdhah, Bishan, Singapore: Muslim Identity With A Contemporary Image - Mohyuddin, Amira; Lamit, Hasanuddin (Faculty of Built Environment, 2008)
Despite a considerable amount of research into the pivotal role of masjid in urban place as an image and identity of a community, there remains a divergence between the available space/place and users' needs. The predominant architectural and planning perspective is more focused on the architectural design and planning of masjid rather than the users. In order to deliver better community places appropriate to the needs of contemporary users it is imperative to gain the perspective of users. The purpose of this research was to explore and understand the phenomenon: physical and psychological values that users associate with masjid as a community place in giving character/identity to the community place, which gives identity to the urban place. An exploratory qualitative case study design was used and data were collected by semi-structured interviews. The interviews were transcribed verbatim and analysed according to content analysis. It was found that the Singapore Muslim community is proud of the new image of their new masjid to the effect that it projects of manifests a contemporary cultural, social and religious identity in the context of a contemporary urban setting. A number of themes of physical and psychological values were generated from the analysis to explain users' views about their masjis as a community place. The new image of masjid disseminates better Muslim community identity to the urban place which reflects the contemporary urban character of the community.